2018
DOI: 10.22260/isarc2018/0155
|View full text |Cite
|
Sign up to set email alerts
|

Computational Workspaces Management: A Workflow to Integrate Workspaces Dynamic Planning with 4D BIM

Abstract: An effective realization of a building construction project-without incurring in congested site areas or decline of productivity-tightly depends on the construction activities planning process that, should consider and manage site workspaces availabilities. In this context, in the past couple of decades many research efforts have been spent in BIM which represents the process of preparation and use of a computer-generated Building Information Model (BIM) even if effective integrated methodologies and models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Choi et al [14] proposed a method that classifies workspaces as fixed workspaces or flexible workspaces based on workspace movability and identifies workspace requirements and storage space requirements for executing activities from a 4D BIM model. Getuli et al [15] introduced a 4D BIM model for automatically creating workspaces based on the space syntax analysis.…”
Section: Current State Of Space-constrained Schedulingmentioning
confidence: 99%
“…Choi et al [14] proposed a method that classifies workspaces as fixed workspaces or flexible workspaces based on workspace movability and identifies workspace requirements and storage space requirements for executing activities from a 4D BIM model. Getuli et al [15] introduced a 4D BIM model for automatically creating workspaces based on the space syntax analysis.…”
Section: Current State Of Space-constrained Schedulingmentioning
confidence: 99%
“…For this reasons, acknowledging building information modeling (BIM) as the leading methodology and the common technological ground for the digitization of the construction sector through innovative applications in every industry field (Newman et al , 2020), from real-time sensor integration for thermal efficiency (Birgonul, 2021; Kumar et al , 2020) and implementation of advanced technologies and methodologies for project inspection, documentation and management (Elghaish et al , 2020; Getuli et al , 2021; Götz et al , 2020; Mansuri and Patel, 2021) to multi-purpose integration of the advanced visualization technologies (Alizadehsalehi et al , 2020; Getuli and Capone, 2018; Pour Rahimian et al , 2020), comprising construction and safety management (Getuli, 2020; Getuli et al , 2016, 2017; Martínez-Aires et al , 2018), the authors already identified in previous works the opportunity to foster the administration of VR safety training with the integration of BIM and game technology (Getuli et al , 2018, 2019). Moreover, to demonstrate a large-scale feasibility of immersive VR for workers’ safety training, an implementation protocol for planning, management and administration of HS contents with BIM and VR has been proposed and tested on a real case study project (Getuli et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Automatic rule checking: design assessment based on the use of computer programs to asses a design and objects configuration with regulations via specific algorithms and BIM-compliant platforms (Getuli et al , 2017; Schwabe et al , 2019). 4D BIM: Construction schedule information integrated into a 3D BIM to increase dynamic visualization of safety procedure (Getuli and Capone, 2018; Boton, 2018; Choe and Leite, 2017; Sheikhkhoshkar et al 2019). Clash detection: for a safety design purpose, clash detection is mostly used for construction workspaces planning and management.…”
Section: Introductionmentioning
confidence: 99%
“…4D BIM: Construction schedule information integrated into a 3D BIM to increase dynamic visualization of safety procedure (Getuli and Capone, 2018; Boton, 2018; Choe and Leite, 2017; Sheikhkhoshkar et al 2019).…”
Section: Introductionmentioning
confidence: 99%